2021
DOI: 10.1186/s12967-021-03168-8
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics approach to COVID-19: a domain-based literature review

Abstract: Background Omics data, driven by rapid advances in laboratory techniques, have been generated very quickly during the COVID-19 pandemic. Our aim is to use omics data to highlight the involvement of specific pathways, as well as that of cell types and organs, in the pathophysiology of COVID-19, and to highlight their links with clinical phenotypes of SARS-CoV-2 infection. Methods The analysis was based on the domain model, where for domain it is int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerges in 2019, causing the actual COronaVIrus Disease 2019 (COVID-19) pandemic. The clinical manifestations are wide from asymptomatic to mild infection of the upper respiratory tract until the severe respiratory failure that requires intensive care unit hospitalization (1)(2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerges in 2019, causing the actual COronaVIrus Disease 2019 (COVID-19) pandemic. The clinical manifestations are wide from asymptomatic to mild infection of the upper respiratory tract until the severe respiratory failure that requires intensive care unit hospitalization (1)(2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the vast majority of multi-omics studies of COVID-19 have focused on single biofluids, typically via proteomic and metabolomic analyses of blood 32 . Whilst blood-based pathway alterations are now well-described, especially dyslipidemia, amino acid dysregulation 33 , inflammatory responses, neutrophil activation and degranulation, and platelet degranulation 34 , other biofluids have not been investigated to the same degree. In this study sebum lipids showed patterns of strong correlation with serum metabolites in controls, but with major changes in COVID-19 positive participants, revealing disease-driven dysregulation in both biofluids.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, multi-omics studies have proven a powerful and successful strategy to provide a broader perspective in understanding disease development and biological phenomena. Several multi-omics analyses of Covid-19 have been proposed to integrate multiple "omes" data to unravel disease mechanisms at multiple omics levels (Overmyer et al 2021;Su et al 2020;Montaldo et al 2021;P. Wu, Chen, et al 2021;Stephenson et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, multi-omics studies have proven a powerful and successful strategy to provide a broader perspective in understanding disease development and biological phenomena. Several multi-omics analyses of Covid-19 have been proposed to integrate multiple “omes” data to unravel disease mechanisms at multiple omics levels (Overmyer et al 2021; Su et al 2020; Montaldo et al 2021; P. Wu, Chen, et al 2021; Stephenson et al 2021). The integrative analyses of rare genome and other “omes” data (e.g., proteome, transcriptome, epigenome, metabolome, and microbiome) may inspire us to discover new risk factors for severe Covid-19 disease.…”
Section: Discussionmentioning
confidence: 99%